Some law enforcement officers' negative attitudes toward overdose victims are exacerbated following overdose education training. (2nd September 2020) - Winograd, Rachel P.; Stringfellow, Erin J.; Phillips, Sarah K.; Wood, Claire A.
ABSTRACT: Background: The devastating impact of the current opioid overdose crisis has led to new involvement of law enforcement officers. Training programs have focused on overdose recognition and response without targeting core attitudinal change by covering addiction or harm reduction principles. Objectives: This study examined the impact of a comprehensive overdose education and naloxone distribution (OEND) training on officers' attitudes toward overdose victims, knowledge of and competence to respond to an opioid overdose, and concerns about using naloxone. The training included the common information about overdose recognition and response, with added components covering broader content about addiction and harm reduction principles and philosophies. Methods: A total of 787 (83% male) officers were administered surveys before and after attending a 2.5–3 hour comprehensive OEND training. Survey items measured overdose-related knowledge and attitudes, including attitudes about people who use drugs and who overdose. Results: Following the training, participants' overdose-related knowledge and perceived competence to use naloxone improved. However, there were more nuanced changes in attitudes toward overdose victims: though 55.3% of officers reported more positive post-training attitudes, 31% reported more negative attitudes, and 13.7% reported no attitudinal change. Younger officers were most likely to report worsened attitudes. Improvements in attitudes toward overdose victims were associated with reductions in both naloxone-related concerns and risk compensation beliefs. Conclusions: Despite a comprehensive OEND training that addressed addiction and harm reduction and directly targeted hypothesized drivers of negative attitudes (e.g., risk compensation beliefs), some officers' attitudes worsened after the training. Randomized experiments of different training approaches would elucidate the mediators and moderators underlying these unexpected responses.